A critical analysis of respondent quotes used as titles of qualitative research papers that are published in peer-reviewed journals. (17th February 2022) - Parkin, Stephen; Kimergård, Andreas
ABSTRACT: The use of respondent quotes to headline qualitative research papers is a popular literary device found in many academic journals. This practice has increased over the last four decades and now appears normalised within qualitative research writing. This article provides a critical analysis of this trend in academic writing and concomitant publishing. Content and framework analyses of 40 papers employing this literary device to summarise the respective studies identified (i) a lack of methodological rigor, (ii) incomplete analysis, (iii) an overall mis-representation of the wider qualitative dataset, and (iv) possible investigator bias associated with using respondent quotes as titles of qualitative research papers. This article questions the credibility of purposely selecting a single experience that reduces the wider collective experience into one deterministic statement. This article contends that such practice is antithetical to the principles of qualitative research. Recommendations are provided to better monitor this practice throughout the academy.